Making Of Digital Assessments Using Wizer.Me In The Pbl Learning Model To Measure High School Student’s Critical Thinking Abilities On Temperature And Heat Materials - Faradila, Halimatul (Department of Physics Universitas Negeri Padang, 2025)
Through the use of the Wizer.me digital platform and the Problem Based Learning (PBL) learning model, this study attempts to develop a digital evaluation to gauge high school students' critical thinking abilities about temperature and heat. The Plomp development model, which comprises a development or prototype stage and a preliminary research stage, was used in the study's Research and Development (R&D) methodology. At SMA Negeri 1 Banuhampu, teacher interviews and the students' initial critical thinking ability tests were analyzed as part of the preliminary research stage. The findings of the investigation demonstrated that pupils' critical thinking abilities remained weak. Additionally, students' comprehension of temperature and heat concepts was also comparatively inadequate, and schools had not fully adopted digital evaluations. Based on these findings, a digital assessment prototype was developed that was made according to Ennis's critical Based on these results, a digital assessment prototype was created using the syntax of the PBL paradigm and Ennis' critical thinking markers. This digital evaluation makes use of five PBL model syntaxes. Using Aiken's V formula, three physics lecturers evaluated the assessment prototype. The results showed that the content, language, presentation, and graphics aspects of the assessment fell into the extremely valid category. The product revision incorporates the validators' suggestions and input. The study's findings show that the digital assessment with essay questions is appropriate for use as a tool to gauge students' critical thinking abilities about heat and temperature. In order to promote the development of 21st-century abilities, this study suggests using essay-based digital evaluations in physics education.